Crystal Structure and Microwave Dielectric Properties of LiRE9(SiO4)6O2 Ceramics (RE = La, Pr, Nd, Sm, Eu, Gd, and Er). Issue 5 (1st March 2013) - Manu, Kurusaroor Mana; Karthik, Chinnathambi; Leu, Lii‐Cherng; Lazar, Kokken Anlin; Ubic, Rick; Sebastian, Mailadil Thomas; Tan, X.
<x xml:space="preserve">Abstract</x> The crystal structure and microwave dielectric properties of apatite‐type LiRE9(SiO4)6O2 ceramics (RE = La, Pr, Nd, Sm, Eu, Gd, and Er) have been investigated. The densification of lithium apatites has been greatly improved with the addition of 1 wt% LiF. Selected area electron diffraction and X‐ray diffraction (XRD) Rietveld analysis confirm that these compounds belong to the P63/m (No. 176) space group with hexagonal crystal symmetry. The porosity‐corrected relative permittivity was found to decrease with decreasing ionic polarizability of RE3+ ions. Relationships between the structural parameters and microwave dielectric properties have been examined. The observed variation in the quality factor of LiRE9(SiO4)6O2 + 1 wt% LiF ceramics (RE = La, Pr, and Nd) was correlated with average cation covalency (%). The temperature coefficient of resonant frequency was found to depend on the bond valence sum of cations. LiEr9(SiO4)6O2 + 1 wt% LiF ceramics showed good microwave dielectric properties with εr = 12.8, Qu × f = 13000 GHz and τf = +17 ppm/°C. All the compositions showed low coefficient of thermal expansion with thermal conductivity in the range 1.3–2.8 W (m K)−1.